Creating sustainable community programs : examples of collaborative public administration - Daniels, Mark Ross, 1952- (Praeger, 2001)
Daniels provides a collection of in-depth case studies of tested sustainable community programs and offers guidance to students regarding successful implementation strategies. He and his contributors look at a variety of sustainable community programs that have been successfully implemented in local communities. While most of these programs exist through government funding or regulation, one--"Food Gatherers"--Is a purely voluntary, non-profit program without any government funding